Direct traumatic optic neuropathy in a temporal laceration: A case report. (January 2017) - Grant, Simon WJ; Halsnad, Moorthy; Colley, Steve; Sharp, Ian
Facial lacerations are a common presentation in emergency departments. It is important to appreciate the mechanism of injury and the anatomy of structures involved in penetrating lacerations in the maxillofacial region. A 65-year-old man suffered an accidental penetrating injury with a sharp kitchen knife to the right temporal region. There was a single laceration to the right temporal region. The right eye had no perception to light, a total afferent and efferent pupillary defect and partial ophthalmoplegia. Computerised tomography scan revealed signs of penetration through the skin, temporalis, postero-lateral orbital wall and orbital apex. There was no injury to the globe or either retrobulbar or intracranial haemorrhage. A diagnosis of direct traumatic optic neuropathy was made following consultation with opthalmology and neurosurgery teams. Only two similar cases of penetrating trauma in the temporal region resulting in direct traumatic optic neuropathy have been identified in the literature. This case presentation highlights the structures that are at risk of damage from penetrating trauma in the maxillofacial region.